Sound intensity mapping on single cylinder direct injection diesel engine with the application of palm oil methyl ester biodiesel - M. S. M., Sani; J. M., Zikri; Abdul Adam, Abdullah (Penerbit Universiti Malaysia Pahang, 2021)
The utilisation of biodiesel nowadays has become familiar with rapid production types of biodiesel in order to replace the dependency on the fossil fuel parallel to the implementation of green technology that emphasises the products to be more environmental-friendly. Nevertheless, the emerges of various kinds of biodiesel cannot be simply used, despite using the biodiesel does not need any major modification on the engine; it still needs a few analyses that must be done to determine whether it will give advantages or disadvantages. Therefore, this research was carried out to investigate the effect of using palm oil methyl ester (POME) biodiesel on the engine in terms of noise emission. The sound intensity mapping method was used to indicate the effectiveness of the biodiesel by identifying the noise radiation. Along with the mapping, the sound power level (SPL) is also being obtained to provide a clear comparison between the parameters. Generally, switching up the engine speed and load increased the sound power level. Based on the results obtained related to the SPL, the intensity mapping tends to show a higher colour-coded in the noise source image for the higher engine speed and load setup. It was found that the engine speed and load give a significant contribution to noise emission produced by the engine, and it can be inferred that this method can be utilised to accomplish the noise emission analysis.